2018
DOI: 10.1038/s41598-018-26512-3
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of e-CAS cell line reveals they are mouse macrophages

Abstract: The 3Rs principles (Replacement, Reduction and Refinement) are focused on finding alternatives to the use of animals in research. In this regard, cell lines are popular and useful tools for the replacement of primary cells in in vitro studies. However, around 15–30% of cell lines used in research have been misidentified or cross-contaminated generating concerns about the results obtained from experiments that use them. Here we described how old aliquots of an equine macrophage cell line (e-CAS) stored at the A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…21,[60][61][62] We which can result in molecular and cellular changes in the cell line. 69 These problems have very recently been highlighted by Evans et al, 70 who sequenced the e-CAS cell line and found the cells to likely be of mouse rather than horse origin. Finally, equine bone marrow-derived mononuclear cells have also been used in cell therapy methodologies in horses affected with equine asthma, whereby intratracheal administration ameliorates the inflammatory response in the lungs, resulting in beneficial effects on clinical signs.…”
Section: F I G U R E 1 Summary Of Macrophage Functionsmentioning
confidence: 99%
“…21,[60][61][62] We which can result in molecular and cellular changes in the cell line. 69 These problems have very recently been highlighted by Evans et al, 70 who sequenced the e-CAS cell line and found the cells to likely be of mouse rather than horse origin. Finally, equine bone marrow-derived mononuclear cells have also been used in cell therapy methodologies in horses affected with equine asthma, whereby intratracheal administration ameliorates the inflammatory response in the lungs, resulting in beneficial effects on clinical signs.…”
Section: F I G U R E 1 Summary Of Macrophage Functionsmentioning
confidence: 99%
“…Предпринимались попытки создать иммортализованные (бессмертные) культуры макрофагов собаки (DH82) (2) и лошади (EML-3C, e-Cas) (3,4), чувствительных к инфекционной анемии, которые депонированы в Американскую Коллекцию культур клеток (American Type Culture Collection, ATCC®, https://www.lgcstandards-atcc.org/Products/Cells_and_Microorganisms/Cell_Lines.aspx?geo_country=ru). Однако оказалось, что линия перевиваемых макрофагов лошади e-Cas -это мышиные макрофаги (5). В связи с этим получение макрофагов в процессе направленной дифференцировки мышиных эмбриональных стволовых клеток (ЭСК) in vitro, в том числе генетически-трансформированных генами лошади, представляет интерес для ветеринарии.…”
unclassified